The Mediating Effect of Stakeholders Support System on the Relationship Between Polytechnics and Entrepreneurial Intentions among Polytechnics Students in Northeast Geo-Political Zone of Nigeria - Buba, Ibrahim Bukar; Bukar, Kagu; Musa, Danladi Ibrahim; Saleh, Ibrahim Usman (International Journal of Engineering and Technology, 2018)
Present global drives toward developing fresh emerging skill-based man power with full entrepreneurial potentials polytechnics are both key and frontiers particularly in developing economies. The literature on entrepreneurial education has confirmed a positive relationship between polytechnics and entrepreneurial intentions development. Yet the boundary conditions for such linkage are less examined in the context of emerging countries. This study draws on resource-based theory to advance stakeholder’s support systems such as: government, parents and financial accesses as a mediator of the relationship between polytechnics and entrepreneurial intentions development. The study used quota sampling for sample selection. This theoretically derived research model is empirically tested using survey data from 291 polytechnics students from six polytechnics in North eastern Nigeria. Partial Least Squares (PLS) algorithm and bootstrap techniques were used to test the study hypotheses. Our empirical findings suggest significant positive relationship between polytechnics education and entrepreneurial intentions. Similarly, stakeholders support systems were found to passively mediates the relationship between polytechnics education and entrepreneurial intentions. The findings of this study will benefit polytechnics administrators, lecturers as well as regulatory agencies and government at all levels and will also serve as frame of reference to future studies.